Using Gamification to Teach Cybersecurity in a Social Science Course: An Experience Paper - Roderick Graham; Medina Williams (Journal of Cybersecurity Education, Research & Practice)
Meta-reviews of gamification suggest that gamifying course instruction can positively impact learners' behaviors and attitudes, leading to improved learning outcomes. However, there is a lack of literature relaying concrete experiences with developing and deploying gamified content. This experience paper contributes to filling that gap by describing the deployment of gamified instruction to students enrolled in a mid-level university social science course. These experiences are organized around four more or less chronological questions the project team needed to answer: (1) why gamify – or what is the rationale for undertaking such an endeavor, (2) what content should be gamified, (3) what design should the gamified content take, and (4) what technologies should be used to develop and deploy the content? We conclude by discussing the importance of grounding gamification in theory and the utility of the hub and spoke design framework used by the project team.